Thermal evaluation of flow channels with perforated-baffles - Eiamsa-ard, Smith; Phila, Arnut; Wongcharee, Khwanchit; Pimsarn, Monsak; Maruyama, Naoki; Hirota, Masafumi (My University, 2023)
The influences of perforated-baffles on the local Nusselt number (Nu) and thermo-hydraulic behaviors were comprehensively studied using thermochromic liquid crystal sheet. The perforated-baffles were designed in two forms: perforated-baffle (PB) and perforated-baffle with square wings (SW-PBs). Transverse solid baffles (TBs) were also tested for an assessment. All baffles had an identical height of 12 mm (e/H = 0.3). Experimental results showed that SW-PBs offered better Nu than PBs. It is also seen that PBs and SW-PBs caused lower pressure loss than TBs by around 20.49% and 13.98%, respectively. The reduction of friction loss was primarily due to the baffle perforation. In addition, the PBs yielded the thermal performance factors (TPF) up to 1.01 at the lowest Reynolds number of 6000.
Keywords: Channel; Heat transfer; Impinging jet; Perforated-baffle; Recirculation; Thermal evaluation